Choline Diet and Its Gut Microbe–Derived Metabolite, Trimethylamine N-Oxide, Exacerbate Pressure Overload–Induced Heart Failure. (January 2016) - Organ, Chelsea L.; Otsuka, Hiroyuki; Bhushan, Shashi; Wang, Zeneng; Bradley, Jessica; Trivedi, Rishi; Polhemus, David J.; Tang, W.H. Wilson; Wu, Yuping; Hazen, Stanley L.; Lefer, David J.
Abstract : Background—: Trimethylamine N-oxide (TMAO), a gut microbe–dependent metabolite of dietary choline and other trimethylamine-containing nutrients, is both elevated in the circulation of patients having heart failure and heralds worse overall prognosis. In animal studies, dietary choline or TMAO significantly accelerates atherosclerotic lesion development in ApoE-deficient mice, and reduction in TMAO levels inhibits atherosclerosis development in the low-density lipoprotein receptor knockout mouse. Methods and Results—: C57BL6/J mice were fed either a control diet, a diet containing choline (1.2%) or a diet containing TMAO (0.12%) starting 3 weeks before surgical transverse aortic constriction. Mice were studied for 12 weeks after transverse aortic constriction. Cardiac function and left ventricular structure were monitored at 3-week intervals using echocardiography. Twelve weeks post transverse aortic constriction, myocardial tissues were collected to evaluate cardiac and vascular fibrosis, and blood samples were evaluated for cardiac brain natriuretic peptide, choline, and TMAO levels. Pulmonary edema, cardiac enlargement, and left ventricular ejection fraction were significantly ( P <0.05, each) worse in mice fed either TMAO- or choline-supplemented diets when compared with the control diet. In addition, myocardial fibrosis was also significantly greater ( P <0.01, each) in the TMAO and choline groups relative to controls. Conclusions—: Heart failure severity is significantly enhanced in mice fed diets supplemented with either choline or the gut microbe–dependent metabolite TMAO. The present results suggest that additional studies are warranted examining whether gut microbiota and the dietary choline→TMAO pathway contribute to increased heart failure susceptibility. Abstract : Supplemental Digital Content is available in the text.